2006
DOI: 10.1016/j.cell.2006.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Presenilins Form ER Ca2+ Leak Channels, a Function Disrupted by Familial Alzheimer's Disease-Linked Mutations

Abstract: Alzheimer's disease (AD) is a progressive and irreversible neurodegenerative disorder. Mutations in presenilins 1 and 2 (PS1 and PS2) account for approximately 40% of familial AD (FAD) cases. FAD mutations and genetic deletions of presenilins have been associated with calcium (Ca(2+)) signaling abnormalities. We demonstrate that wild-type presenilins, but not PS1-M146V and PS2-N141I FAD mutants, can form low-conductance divalent-cation-permeable ion channels in planar lipid bilayers. In experiments with PS1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
688
7
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 629 publications
(750 citation statements)
references
References 43 publications
44
688
7
8
Order By: Relevance
“…This effect is distinct from the other known effects of phosphorylation on both vertebrate and Drosophila LTCCs in which the current-voltage relationships and/or channel activation and inactivation are also affected (77,80). It was suggested recently that presenilin also forms ER Ca 2ϩ leak channels, a function quite distinct from its recognized activity as an intramembranous aspartyl protease (81). In accordance with this model, altered intracellular Ca 2ϩ levels due to the inability of mutant presenilins to conduct Ca 2ϩ properly might affect the tail current via Ca 2ϩ -dependent inactivation of the LTCC.…”
Section: Discussionmentioning
confidence: 74%
“…This effect is distinct from the other known effects of phosphorylation on both vertebrate and Drosophila LTCCs in which the current-voltage relationships and/or channel activation and inactivation are also affected (77,80). It was suggested recently that presenilin also forms ER Ca 2ϩ leak channels, a function quite distinct from its recognized activity as an intramembranous aspartyl protease (81). In accordance with this model, altered intracellular Ca 2ϩ levels due to the inability of mutant presenilins to conduct Ca 2ϩ properly might affect the tail current via Ca 2ϩ -dependent inactivation of the LTCC.…”
Section: Discussionmentioning
confidence: 74%
“…We have recently shown that ␥-secretase activity is essential for adult ␤-cell survival (21). Multiple studies have linked the ␥-secretase-independent presenilin activity to the control of ER Ca 2ϩ release under basal conditions and during caspase-3-mediated apoptosis (53)(54)(55). In general, the presenilin-1 gain-of-function mutations in Alzheimer disease lead to an overload of releasable ER Ca 2ϩ , while presenilin-2 mutations have been reported to decrease Ca 2ϩ stores (56).…”
Section: Discussionmentioning
confidence: 99%
“…58 The channels responsible for the passive leak remain to be properly characterized, but there is increasing evidence that presenilins may be leak channels. 45,59 The mutated forms of PS1 that give rise to early-onset FAD reduced the passive leak resulting in enhanced Ca 2+ signals. 59 The mutated PS1 can also interact with the Ins(1,4,5)P 3 R to enhance its sensitivity.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…45,59 The mutated forms of PS1 that give rise to early-onset FAD reduced the passive leak resulting in enhanced Ca 2+ signals. 59 The mutated PS1 can also interact with the Ins(1,4,5)P 3 R to enhance its sensitivity. 60,61 Another important remodeling event associated with AD is a downregulation of the Ca 2+ buffer calbindin D-28k (CB).…”
Section: Bipolar Disordermentioning
confidence: 99%